Reply to the letter : To consider the exercise density in the dose–response relationship: the idea is promising, the operationalization tricky! - Fabian Herold; Liye Zou; Paula Theobald; Patrick Manser; Ryan S. Falck; Qian Yu; Teresa Liu-Ambrose; Arthur F. Kramer; Kirk I. Erickson; Boris Cheval; Yanxia Chen; Matthew Heath; et al. (European Journal of Applied Physiology, 2026)

Beyond FITT: addressing density in understanding the dose–response relationships of physical activity with health—an example based on brain health - Fabian Herold; Liye Zou; Paula Theobald; Patrick Manser; Ryan S. Falck; Qian Yu; Teresa Liu-Ambrose; Arthur F. Kramer; Kirk I. Erickson; Boris Cheval; Yanxia Chen; Matthew Heath; et al. (European Journal of Applied Physiology, 2025)
Research on physical activity (PA) and health has a fundamental concern with dose–response relationships. The variables of (1) Frequency, (2) Intensity, (3) Time, and (4) Type (i.e., the FITT principle) have traditionally been used to operationalize the dosage of PA. We consider some limitations of FITT and propose that it can be complemented by the additional variable density (from the German exercise and training variable Belastungsdichte), which can be defined as the timing of successive work bouts within a single PA bout as well as the timing between successive PA bouts within a specific time period; it does so by quantifying the temporal intervals between successive work or PA bouts (i.e., time spent at a lower PA intensity or resting such as in napping/sleeping or sedentary behaviors). Using the field of PA and brain health as an example, we discuss the opportunities and challenges for further research employing the variable density and consider its potential to improve the understanding of dose–response relationships between PA and health outcomes.

Comparison of the acute effects of breaking up prolonged sitting time with single-task or a dual-task walking on cognitive function and cerebral blood flow in older adults: a randomized crossover trial - Paolo M. Cunha; Gustavo O. Silva; Liye Zou; Max D. Oliveira; Hélcio Kanegusuku; Qian Yu; Yanxia Chen; Zhihao Zhang; Fabian Herold; Ryan S. Falck; Boris Cheval; Olivier Dupuy; et al. (GeroScience, 2025)